Ethical Imperatives in Global Business Leadership - Muhammed, Khalid Hussen; Abbas, Zeyad Ali; Yassen, Muzaffer; Alkabi, Hameed Salim (Journal of Ecohumanism, 2024)
Background: Ethical responsibilities and leadership strategies are interconnected in today’s global business landscape. This association raises substantial ethical problems in corporate decision-making. Objective: The article explores how ethical imperatives influence the leadership strategies of multinational organizations to tackle global business difficulties and promote ethical leadership. Methodology: This study collected a large dataset using a mixed-methods approach, including case studies, questionnaires, and interviews. Having a variety of methods allows for a thorough analysis of the activities of multinational corporations in a wide range of sectors and locations. Results: The study revealed a strong link between ethical responsibilities and leadership efficacy, especially among international companies. Integrity and success in business increasingly depend on ethical leadership, which involves openness, engaging stakeholders, impartially resolving challenges, and promoting social and environmental sustainability. Conclusion: The article emphasizes that ethical leadership is crucial for maintaining social peace, corporate sustainability, and company reputation. The study promotes the development of ethical decision-making cultures and offers practical advice for legislators, educators, and business leaders. This adds to the discussion on potential new leadership models by suggesting that focusing on ethical values in management might make firms more transparent and lead to long-term profitability.